The Influence of Commercial Activities and Tourism Activities on the Development of Public Facilities of the Simpang Barelang Boundar - Fermana, Andhika Pradita; Sidabutar, Yuanita FD (Borong Newinera Publisher, 2024)
This research aims to evaluate the influence of commercial activities and tourism activities on the development of public facilities at the Simpang Barelang Roundabout, a strategic area that connects several areas in the Batam region. The method used in this research is a quantitative method with a descriptive approach. Primary data was collected through surveys involving business actors, tourists and local communities. The survey was designed to identify their needs and perceptions of available public facilities. In addition, secondary data was obtained from local government reports and other related institutions.The analysis results show that commercial activities, which include trade, services and small industry, significantly influence the need for adequate infrastructure. The increase in the number of businesses around the Simpang Barelang roundabout encourages the government to provide facilities such as better roads, street lighting and adequate drainage systems. On the other hand, increasing tourism activities in this area also contribute to the development of public facilities. Tourists who visit, both domestic and international, expect adequate facilities such as a large parking area, tourist information center, cleaning facilities and recreation areas. This research concludes that synergy between commercial and tourism activities is very important in the planning and development of sustainable public facilities.